Survival Language of Teenagers in Coastal Families in Sandi Village, Wakatobi District - Djamudi, Nadir La; Iye, Risman; Abida, Fithriyah Inda Nur (JOLLT Journal of Languages and Language Teaching, 2024)
This research aims to describe the curses used by teenagers in the coastal area of Sandi Village, South Kaledupa District, Wakatobi Regency. The study is expected to contribute to the researcher's knowledge in the field of linguistics. The research data consists of utterances containing curses. The informants for this study were 15 individuals, comprising 8 females and 7 males aged between 12 to 18 years. This field research utilized a qualitative descriptive approach with data collection techniques including recording, listening, and note-taking. The study reveals that there are two forms of curses used by teenagers in Sandi Village, namely curses in the form of words and phrases. Curses used by teenagers in coastal families of Sandi Village can be categorized into three types: first, curses in the form of words, consisting of 14 words such as Pei (fool), Deppe (snub-nosed), kumbou (monitor lizard), Tajo (genitals), Kaffiri (infidel), Kajilo (cross-eyed), Dhobba (fat), Onitu (devil), Beka (cat), Jahannamu (damned), setani (devil), pogko (skink), Te saa (snake), and Te ibilisi (demon). Second, curses in the form of phrases, with 10 instances such as Mata kajilou (Your eyes are cross-eyed), Kapatuli pei (naughty fool), Usauri Kabeo-beo (extremely foolish), Kaleau (your genitals), Te ngarou (your mouth), Lengka nuyi ina (your mother's genitals), Teyi ama (your father), Botau (your bald head), Morusu koppe (skinny and bony), Morusu dao (ugly and skinny), Unimmiu (your vagina), sauri konduo (too crazy), teana harramu (illegitimate child), Lombu nu ngaro (mouth hole). It is important to note that some words and phrases might have specific cultural or regional meanings that are crucial to understanding the context of this research.